Improvement Of Melting And Crystallisation Properties Of Rambutan Seed Fat As Cocoa Butter Improver By Two‐stage Fractionation Technique - F. Azzatul; M.H.A. Jahurul; J. Norliza; M.R. Norazlina; M. Hasmadi; Patricia Matanjun; Jau-Shya Lee; A. Shihabul; Noorakmar Ab. Wahab; Sharifudin Md Shaarani (Institute of Food Science and Technology, United States, 2024)
International Journal of Food Science & TechnologyVolume 56, Issue 4 p. 1574-1581